Emergence of a New Era in Orthopaedic and Spine Medicine: Advancements and Specialization in Pakistan's Healthcare Landscape - Samir Khan Kabir (Gandhara University, 2023)
In a remarkable transformation, the landscape of medical science, including Orthopaedic and Spine care, is rapidly evolving. Even in regions like Pakistan, characterized as third-world countries, healthcare is swiftly adopting the latest techniques, technologies, and research predominantly originating from the Western world. The origins of Orthopaedic Surgery in Pakistan trace back to the era when General Surgeons initially handled these responsibilities. However, the true development of Orthopaedic specialization began in the 1970s when the necessity for dedicated Orthopaedic treatment became evident. This marked the inception of the Orthopaedic era in the country. By the early 2000s, many medical professionals opted for this specialization, leading to a saturation point that paved the way for sub-specializations within Orthopaedics. These sub-specialities include Periotic, Trauma, Hand, Oncology, Arthroplasty, Sports, and Spine.1 Between 2000 and 2015, these sub-specialties also progressed to a saturation point, prompting a demand for even more specialized expertise. Over the past 5 to 8 years, each sub-speciality has further fragmented, with individuals or teams dedicated to refining systems that provide superior management of pathologies, thus enhancing prognoses and patient outcomes.2  This evolution has seen the emergence of both sub-specialties and super-specialties, reflecting the contemporary medical practice needs. The trajectory is clear: as exposure and practical experience accumulate, a cadre of experts will naturally emerge within these specialized domains.   The domain of Spine specialization, once regarded with apprehension due to its challenging nature and variable outcomes, has been revolutionized by integrating cutting-edge technology, advanced surgical techniques, and in-depth research. Distinct categories within the Spine speciality have emerged, spanning Trauma, Oncology, Deformity Correction, Degenerative Spine, and Infection.3 These intricate surgeries are now performed using minimally invasive techniques, informed by meticulous research prioritizing anatomical precision. These advancements involve smaller incisions, real-time X-ray guidance, and even endoscopic approaches for enhanced operative field visualization. This curtails inflammatory responses and expedites patient recovery, facilitating earlier discharge from medical facilities.   A noteworthy addition to Pakistan's Spine surgery landscape is the introduction of Endoscopic Spine Surgery. Over the past half-decade, many Neuro and Orthopaedic Spine Surgeons have sought training in this cutting-edge super-specialty. The procedure offers substantial advantages such as same-day patient discharge and quicker return to normal routines. Presently, only a handful of centres in the country provide this innovative treatment modality, marking a significant stride in Spine care.